Regulation of carcinogenic food additives in the United States - karstadt, Myra L. (European Journal of Oncology and Environmental Health, 2009)
Regulation of food additives, including carcinogenic food additives, in the United States, is the responsibility of the U.S. Food and Drug Administration (FDA). FDA has approved for marketing food additives that have not been demonstrated, using good testing methods, to be free of carcinogenic potential. Acesulfame potassium, a high-intensity artificial sweetener, is widely used in the United States, usually in blends with aspartame or sucralose. Acesulfame has never been tested in bioassays sufficient to resolve the question of whether the additive is free of carcinogenic potential. FDA’s decision-making regarding carcinogenic food additives has not necessarily been based on good science or protection of public health. Changes in the Food Additive Petition (FAP) approval process are needed to ensure that carcinogenic food additives do not get approved for marketing.